Questions: The complex number (-1-sqrt(3) i)^8 is equal to
Select one:
2^7 e^(i pi/3)
2^7+2^7 sqrt(3) i
-2^7-2^7 sqrt(3) i
2^8 e^(i 2/3 pi)
-2^8+2^8 sqrt(3) i
Transcript text: The complex number $(-1-\sqrt{3} i)^{8}$ is equal to
Select one:
$2^{7} e^{i \frac{\pi}{3}}$
$2^{7}+2^{7} \sqrt{3} i$
$-2^{7}-2^{7} \sqrt{3} i$
$2^{8} e^{i \frac{2}{3} \pi}$
$-2^{8}+2^{8} \sqrt{3} i$
Solution
Solution Steps
Step 1: Convert to Polar Form
To convert the complex number \(-1 - \sqrt{3} i\) to polar form, we first calculate the modulus \(r\) and the argument \(\theta\). The modulus is given by:
\[
r = |z| = \sqrt{(-1)^2 + (-\sqrt{3})^2} = \sqrt{1 + 3} = \sqrt{4} = 2
\]
The argument \(\theta\) can be found using:
\[
\theta = \tan^{-1}\left(\frac{-\sqrt{3}}{-1}\right) = \tan^{-1}(\sqrt{3}) = \frac{\pi}{3}
\]
Since the complex number is in the third quadrant, we adjust \(\theta\) to:
\[
\theta = \pi + \frac{\pi}{3} = \frac{4\pi}{3}
\]
Thus, the polar form is:
\[
-1 - \sqrt{3} i = 2 e^{i \frac{4\pi}{3}}
\]
Step 2: Apply De Moivre's Theorem
Using De Moivre's Theorem, we raise the polar form to the 8th power:
\[
(-1 - \sqrt{3} i)^{8} = (2 e^{i \frac{4\pi}{3}})^{8} = 2^8 e^{i \frac{32\pi}{3}}
\]
Next, we simplify the exponent:
\[
\frac{32\pi}{3} = 10\pi + \frac{2\pi}{3} \quad \text{(since } 10\pi \text{ is a multiple of } 2\pi\text{)}
\]
Thus, we can reduce it to:
\[
e^{i \frac{2\pi}{3}}
\]
Step 3: Final Result
Combining the results, we have:
\[
(-1 - \sqrt{3} i)^{8} = 2^8 e^{i \frac{2\pi}{3}}
\]
This matches the form of the options provided in the original question.